Non-Monotonic Survival of Staphylococcus aureus with Respect to Ciprofloxacin Concentration Arises from Prophage-Dependent Killing of Persisters - Elizabeth L. Sandvik; Christopher H. Fazen; Theresa C. Henry; Wendy W.K. Mok; Mark P. Brynildsen (MDPI AG, 2015)
Staphylococcus aureus is a notorious pathogen with a propensity to cause chronic, non-healing wounds. Bacterial persisters have been implicated in the recalcitrance of S. aureus infections, and this motivated us to examine the persistence of S. aureus to ciprofloxacin, a quinolone antibiotic. Upon treatment of exponential phase S. aureus with ciprofloxacin, we observed that survival was a non-monotonic function of ciprofloxacin concentration. Maximal killing occurred at 1 µg/mL ciprofloxacin, which corresponded to survival that was up to ~40-fold lower than that obtained with concentrations ≥ 5 µg/mL. Investigation of this phenomenon revealed that the non-monotonic response was associated with prophage induction, which facilitated killing of S. aureus persisters. Elimination of prophage induction with tetracycline was found to prevent cell lysis and persister killing. We anticipate that these findings may be useful for the design of quinolone treatments.